Pelatihan Pembuatan Sovenir Berbahan Resin di SMK 10 Nopember Jakarta - Ariyanti, Silvi; Farida, Farida; Prabowo, Herry Agung (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
According to Permendiknas No. 19 of 2005, cultural arts and skills education is given in schools because it is unique, meaningful, and beneficial to the development needs of pupils, and lies in the provision of experience through expressive, creative, and appreciative activities. This statement suggests that learning cultural arts and skills not only focuses on mastering the teaching material but also on enhancing students' creativity by improving their craftsmanship skills. Strategies are needed to encourage students to be creative while learning cultural skills and arts because of the importance of creativity. Approaches, methods, and learning models are crucial in the art learning process at school. By using the right target approach, learning will become more meaningful as it brings us closer to the goal. The purpose of this community service activity is to enhance students' ability to create creative products as well as help them find business opportunities. The students of SMK 10 November Jakarta are the target audience of this community service program. This method of community service is training. The lecturers and students of the study program of Industrial Engineering of Mercu Buana University who have experience in hand craft making with resin materials act as instructors and sources in this activity.